On the degree of holomorphic mappings from an annulus into an annulus - Nguyen Doan Tuan; Pham Viet Duc (Український математичний журнал, 2004)
We establish an estimate for the degree of a holomorphic mapping f : K₁ → K₂ (here, K₁ and K₂ are doubly-connected domains) in terms of the modulus of a family of curves in K₂. This estimate generalizes a result obtained by Kobayashi.